2016
DOI: 10.1515/ntrev-2016-0027
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigations on the control of yam (Dioscorea rotundata Poir) tuber rot through nanoscience

Abstract: Abstractand

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…To enhance the productivity of the agricultural and food sector, applications of the nanomaterials and nanotechnology has been adopted [23] , [147] , [26] , [148] . Several kinds of research have adapted nanomaterials in the area of soil bioremediation, biochar enhancement for soil enrichment, crop protection, fertilizer application, renewable energy system application in agriculture, bio-sensors, disease control, and coating of crop processing system against corrosion to achieve high processing efficiency and crop detoxification [14] , [15] , [16] , [17] , [18] , [19] , [152] . Synthesis mechanism for materials makes use of atomic, fungi, molecular, processing of particulates in vacuum or fluid medium with the fungi method the most widely used due to high cost of adopting other methods [2] , [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the productivity of the agricultural and food sector, applications of the nanomaterials and nanotechnology has been adopted [23] , [147] , [26] , [148] . Several kinds of research have adapted nanomaterials in the area of soil bioremediation, biochar enhancement for soil enrichment, crop protection, fertilizer application, renewable energy system application in agriculture, bio-sensors, disease control, and coating of crop processing system against corrosion to achieve high processing efficiency and crop detoxification [14] , [15] , [16] , [17] , [18] , [19] , [152] . Synthesis mechanism for materials makes use of atomic, fungi, molecular, processing of particulates in vacuum or fluid medium with the fungi method the most widely used due to high cost of adopting other methods [2] , [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The particles displayed potency against cancer cells producing IC50 of 2.6, 4.8 and 6.8 mg/mL against prostate, breast and liver cancer cell lines respectively. Eze et al (2016a) biosynthesized AgNPs (termed Ag Neem nano) using leaf extract of Azadirachta indica. The Ag Neem nano reportedly have a mean particle size of 20 µm.…”
Section: Antioxidant Catalytic and Sensing Activitiesmentioning
confidence: 99%
“…Fresh yams are susceptible to be contaminated by pathogenic and spoilage microorganisms and are not easily stored due to their high water activity and nutrient content. It has been reported that the yam root rot disease caused by Fusarium moniliforme (F. moniliforme) are the major postharvest challenges in the availability of yam root tubers (Eze et al, 2016;Ezeonu et al, 2018;Ogundana & Dennis, 1981;Okigbo & Ikediugwu, 2000). Besides as the spoilage fungi of yam tubers, F. moniliforme can also produce mycotoxin of Fumonisin B 1 (FB 1 ) to contaminate the yam tubers.…”
Section: Introductionmentioning
confidence: 99%